Clinico-epidemiological profile and onychoscopic pattern of nail disorders in geriatric population - Muzalda, Gajendra; Bhatia, Kailash; Namdeo , Chaitanya (International Journal of Research in Dermatology, 2023)
Background: Adequate knowledge about nail changes in the geriatric population can help in the early identification and timely treatment of underlying disease adding to the quality of life of the elderly population with nail concerns. The present study is aimed to study the clinico-epidemiological profile and onychoscopic pattern of nail disorders in geriatric populations. Methods: This observational study included 100 subjects aged 60 years or more. Clinical examination and onychoscopic examination by Dermlite DL4 dermoscope with 10x magnification of the nail bed, nail plate, nail fold, and hyponychium in all the 20 nails were done. Even single positive findings in a single nail are considered in the study. If clinically suspected of onychomycosis, 20% potassium hydroxide mount was performed to identify fungal elements. Results: Mean age of the subjects was 66.27±5.546 years. Male: female ratio was 2.1:1. Mean duration of complaints pertaining to nail changes was 4.7±3.864 years. The damaged cuticles were the universal finding in all the subjects (100%) in nail fold examination, nail dystrophy and longitudinal ridges were seen in all [100.0%)] subjects of nail plate examination. The most frequently observed change in nail bed has been splinter haemorrhage [26% versus. 32%] and in hyponychium was subungual hyperkeratosis [36% versus 37.0%] clinically and dermoscopically respectively. Onychomycosis was diagnosed in 25% of total subjects. Conclusions: Onychoscopy is an important, non-invasive modality to identify and diagnose the nail changes earlier which helps in managing the disease earlier.